Bonneuil: school or therapy? - Petri, Renata (Clinical Styles. The Journal on the vicissitudes of childhood, 1998)
This article is a report of the author experience as a trainee at Bonneuil. It analyses the role of adults on the institutional work with autistic and psychotic children. According to the author, those adults work as educators. They would offer signifiants to the children and be available for identification with them. They wouldn't be the educators of pedagogy, that pursue an ideal, but educators that present themselves as divided, castrated, psychoanalysis-influenced individuals; they would have an analytical hearing that may promote subjective changes on children.